About the conceptual analysis of the verbal word (on a material of a verb to love). (Eurasian Journal of Philology Science and Education, 2015)
In article problems of the conceptual analysis of the word are considered. The cognitive and propositional structure of a concept is established to love, its national and cultural contents. As a result of the analysis the author shows that it is possible to carry out the conceptual analysis on the example of the verbal word. Work has interdisciplinary character, is written on a joint of such sciences, as linguistics and cultural science, cognitive linguistics. The main content of research makes the analysis of the verbal word. In article characteristic signs of theconceptual analysis, its methods and receptions are investigated. The conceptual analysis allows to start studying of the conceptual device of the language conducting to judgment of the world in terms of concepts. Characteristics of a concept and its ways of verbalization are allocated and described. The verbal word codes information having variousconceptual semantics which domination are verbs of the relation of Russian. In work these verbs as possess difficult semantics are staticized and correspond to conceptual concept of the word.
Keywords: verbal word; concept; conceptual analysis; cognitive and propositional structure